Long-term L-Carnitine Administration reduces Erythropoietin Resistance in Chronic Hemodialysis Patients with Thalassemia Minor - Biagio R. Di Iorio; Pasquale Guastaferro; Nicola Cillo; Emanuele Cucciniello; Vincenzo Bellizzi (AboutScience Srl, 2007)
Background and Aim Both thalassemia and carnitine deficiency represent independent causes of erythropoietin resistance, and thus anemia, in uremic patients. We evaluated the unknown long-term effects of L-carnitine administration in β-thalassemic on chronic hemodialysis. Methods We studied twelve subjects (M = 8; F = 4) affected by β-thalassemia minor (β-thal; HbA2 level = 6.6 ± 0.6%) and forty non-thalassemic subjects (M = 24; F = 16) as controls (C), on chronic hemodialysis treatment. Patients and controls were at target hemoglobin levels (11-12g/dl) prior to the study and underwent to i.v. L-carnitine administration for a one year period-time. Results Groups were comparable for age, gender, serum levels of hemoglobin (Hb), iron, ferritine, PTH and aluminum, transferrin saturation, and dialysis modalities. During the study both groups showed significant Hb increase and erythropoietin (EPO) decrease; as a difference, such changes emerged at the 3rd month in C but at the 8th month in β-thal. At start, during the dialysis session the erythrocyte MCV reduced in C but not in β-thal (65.3 ± 3.2 to 65.5 ± 3.2 fl; NS); along carnitine administration period, however, MCV during dialysis decreased also in β-thal, starting since the 9th month of treatment. Conclusion This study provides evidence of the lowering of EPO resistance in β-thalassemia patients on hemodialysis due to long-term carnitine administration. Thus, prolonged carnitine supplementation should be suggested to patients on dialysis affected by β-thalassemia with poorly responsive anemia, or requiring large doses of erythropoietin.